The effect of salt stress on the germination of maize (Zea mays L.) seeds and photosynthetic pigments - Sali ALIU; Imer RUSINOVCI; Shukri FETAHU; Bekim GASHI; Emilija SIMEONOVSKA; Ludvik ROZMAN (Acta Agriculturae Slovenica)
The objective of this study was to investigate the effect of salinity stress on seed germination and chlorophyll content in maize. In the study, two maize hybrids were included (Bc 678 and Bc 408) originating from the Bc Institute at Rugvica near Zagreb (Croatia) and two maize populations (LMP-1 and LMP-2) originating from Kosovo. The experiment was conducted in four replicates of 100 seeds, which were germinated on top of double-layered papers, each with 10 ml of salt solution of NaCl and CaCl2 in Petri dishes. Germinated seeds were counted every 24 h for 15 days. The photosynthetic pigments, chlorophylls ‘a’ and ‘b’ as well as carotenoids were extracted with 80 % acetone. Chlorophyll and carotenoid contents were calculated using absorbance values at 662, 644 and 440 nm. The effects of the NaCl and CaCl2 concentrations accounted for a high proportion of the variance in all analyses. The results showed that both germination percentage and germination index decreased significantly in all cultivars at the highest salt concentrations. The significant differences between different concentrations of salinity were also found in all cultivars for the content of chlorophyll ‘a’ and ‘b’ and for the content of carotenoids.